Phytohormones in microalgae: a new opportunity for microalgal biotechnology? - Lu, Yandu; Xu, Jian (Trends in plant science, 2015)
•New evidence suggests that microalgae possess functional phytohormone metabolic pathways.•Additional signaling mechanisms may be present in microalgae to transmit the hormone signals.•Manipulation of phytohormones in microalgae may represent opportunities for biofuel feedstock development. Phytohormones, including auxin, abscisic acid (ABA), cytokinin (CK), ethylene (ET), and gibberellins (GAs), have been found in a broad spectrum of microalgal lineages. Although the functional role of microalgal endogenous phytohormones remains elusive, molecular evidence from the oleaginous microalga Nannochloropsis oceanica suggests that endogenous ABA and CK are functional and that their physiological effects are similar to those in higher plants. In this Opinion article, proceeding from genome-based metabolic reconstruction, we suggest that modern higher plant phytohormone biosynthesis pathways originate from ancient microalgae even though some of the microalgal phytohormone signaling pathways remain unknown. Dissection and manipulation of microalgal phytohormone systems could offer a new view of phytohormone evolution in plants and present new opportunities in developing microalgal feedstock for biofuels.